Grain refinement of magnesium alloys by dynamic recrystallization (DRX): A review - Hamed Mirzadeh (Journal of Materials Research and Technology, 2023)
For elevated-temperature thermomechanical processing, the occurrence of recrystallization during straining is known as dynamic recrystallization (DRX), which usually happens in Mg alloys during practical hot deformation processes such as rolling, forging, extrusion, friction stir processing (FSP), and multidirectional forging (MDF). Accordingly, the present review paper is dedicated to the grain refinement of Mg alloys by DRX during hot working and summarization of the state-of-the-art. Firstly, the grain refinement of Mg alloys is overviewed, which includes grain refinement achieved during (I) solidification (heterogeneous nucleant particles, growth restriction factor, and ultrasonic treatment), (II) fusion-based and solid-state metal additive manufacturing, (III) annealing of deformed alloys via static recrystallization (SRX), and (IV) severe plastic deformation (SPD). Afterward, the critical conditions for the initiation of DRX, single-peak and multiple-peak (cyclic) flow behaviors, microstructural evolution, and necklace formation during DRX are summarized for Mg alloys. Moreover, the dependency of the DRX grain size and its kinetics to the (I) deformation conditions (temperature and strain rate, as represented by the Zener-Hollomon parameter), (II) initial microstructure (by consideration of continuous and discontinuous DRX mechanisms), (III) alloying elements (solute drag effect), (IV) dynamic precipitation (Zener pinning effect for retardation of grain coarsening), and (V) particle stimulated nucleation (PSN, especially for the Mg alloys containing long period stacking ordered (LPSO) structures and metal-matrix composites) are critically discussed. Furthermore, the metadynamic recrystallization (MDRX) as well as improvement of mechanical properties (represented by the Hall-Petch relationship), enhancement of strength–ductility synergy, and inducing superplasticity for superplastic forming by DRX are overviewed. Finally, the research gaps and distinct suggestions for future works are introduced.